A multi-point constraints based layout design of multi-component systems - Gao Huan-Huan; Zhu Ji-Hong; Zhang Wei-Hong (International Journal for Simulation and Multidisciplinary Design Optimization, 2014)
The primary purpose of this paper was to present an efficient method to implement the layout design of multi-component systems. In this study, two kinds of design variables: topology variables and geometry variables are simultaneously optimized to maximize the structure stiffness. The multi-point constraints (MPC) are used to simulate the connection behavior between these movable components and supporting structure. So during the optimization iterations, mesh regeneration caused by moving components is avoided compared to the linkage of nodal coincidence. At the same time, the precise geometry shapes and properties of components are maintained to reduce the model building error. At the last of the paper, the numerical example is presented to show the validity of this method.